P14.70 BMScope: A systematic mapping review of brain/leptomeningeal metastasis clinical studies from 2010 to 2020. (9th September 2021) - Cheng, V W T; Heywood, R; Zakaria, R; Burger, R; Fitzpatrick, A; Zucker, K; Sanghera, P; Doherty, G J; Palmieri, C; Jenkinson, M D
Abstract: BACKGROUND: Brain metastasis (BM) and leptomeningeal disease (LMD) are typified by a poor prognosis and are an area of unmet clinical need. Historically, patients with central nervous system (CNS) disease have been excluded from systemic therapy clinical trials, particularly with active/leptomeningeal disease. However, increasing prevalence of CNS metastasis is leading to greater interest in BM/LMD. We performed a descriptive analysis of clinical studies investigating BM/LMD management, published between Jan 2010 to Mar 2020. METHODS: A comprehensive, customised search strategy was devised for 12 online bibliographic databases, using the following concepts: "clinical study", "brain metastasis", "leptomeningeal disease", "intervention", "patient-related outcome". Double screening for inclusion/exclusion was performed on the Rayyan QCRI web application. Published abstracts were also screened for inclusion from ASCO, ESMO, SNO and EANO between 2015–2020. Following full text screening, conflicts were resolved by consensus and data were extracted using an online standardised tool. Data analysis and data visualisation were performed on the R statistical package. RESULTS: Overall, 33118 published studies were double screened; 2632 full publications and 628 abstracts were included. Of these, 14.7% reported on unique interventional clinical trials (phase 2 = 267; phase 3 = 80). More than three times the number of clinical trials investigating systemic agents as the sole therapy for BM/LMD were published in Q1 2020 compared to the whole of 2010 (16 vs 5). 42.5% of clinical trials employed a form of local therapy (brain targeted radiotherapy or neurosurgery). Studies reported on patients with BM (n = 2738), LMD (n = 110) or both (n = 119). The majority of studies were performed in North America, Europe or East Asia (88.5% vs 11.5% rest of the world). The top 3 nations involved in published studies were the USA (n = 1155), China (n = 351) and Germany (n = 334). Network analysis demonstrated increasing links between countries. In line with expected BM prevalence, the main tumour sites studied were lung (23.4%), gastrointestinal (17.5%), breast (15%) and melanoma (12.5%). A rising trend of published BM/LMD studies over time was noted, with 83 observational studies/10 clinical trials in 2010 vs. 454 observational studies/80 clinical trials in 2019. CONCLUSION: These findings demonstrate that over the last decade there has been a growth in BM/LMD research; likely reflecting an increasing disease prevalence, availability of novel and potentially CNS active agents, as well as more advanced local therapy modalities. BM/LMD clinical research is dominated by a few geographical regions and nations; however, there is an apparent shift to more international collaboration. This comprehensive mapping exercise will enable targeted systematic reviews of the existing evidence base on BM/LMD management.